Estimation of Diafenthiuron Residues in Cardamom (Elettaria cardamomum (L.) Maton) Using Normal Phase HPLC: Dissipation Pattern and Safe Waiting Period in Green and Cured Cardamom Capsules. (24th February 2014) - Stanley, Johnson; Chandrasekaran, Subramanian; Preetha, Gnanadhas; Kuttalam, Sasthakutty; Jasmine, R. Sheeba
Abstract : Diafenthiuron is an effective insecticide used for pest management in cardamom. Residues of diafenthiuron and its degradation/dissipation pattern in cardamom were determined to work out safe waiting period. Samples were collected after three sprays of diafenthiuron @ 400 and 800 g a.i ha −1 and the residues extracted in acetonitrile and quantified in normal phase HPLC in UV detector. Diafenthiuron was detected in6.61 ± 0.1 min. The limits of detection (LOD) and limits of quantification (LOQ) were determined to be 0.01 and 0.05 μ gmL −1 . The initial deposits were found to be 3.82 and 4.10 μ g g −1 after sprays of diafenthiuron @ 400 g a.i ha −1 in the first and second experiments, respectively. Nearly cent percent of residues dissipated at 10 days after treatment in the recommended dose of diafenthiuron 400 g a.i ha −1 and the half life varied from 2.0 to 2.8 days with a waiting period of 5.5 to 6.7 days in green capsules of cardamom. The waiting period was 5.4 to 7.0 days in cured capsules of cardamom. With harvest being the focal point for enforcement of residue tolerances, the suggested waiting period of seven days is safe without the problem of pesticide residues in harvestable produce.